On the Changes that are Needed in the Professional Teachers' Formation - Andrzej de Tchorzewski (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
Once the school education had become common and mandatory, persons who were engaged in teaching obtained the professional status. In the past, professionalization of teachers occurred under various educational forms. Already in the 18th century, at the universities and academies (in Cracow, and Vilnius), teaching seminars had been organized which, as time passed, became common teachers' educational centres having the status of the secondary schools. In the course of time, they had been transformed into the schools of higher educational level. Paying a lot of attention to the formation of the professional attitudes of the future teachers was a very essential feature of those schools. With hindsight one could say that the teachers' schools strongly insisted on the process of the professional formation of the candidates for this profession. In the second half of the 20th century, the idea of obligatory teachers' education at the level of the higher studies (college and professional ones) prevailed. Along with it, regardless of the official guidelines, the issues regarding the selection of the candidates for this profession were pushed on the back of the teachers' education, together with the issues regarding their professional predispositions and development of the ethical and moral attitudes that provide for the teachers' professional ethos. Blameworthy behaviour of certain teachers educators is the direct result of that process, which is being noticed by the society, especially, the parents. Furthermore, such behaviour has become the subject matter of the evaluation in the common courts. Easy access to the profession of a teacher has resulted in its degradation in public awareness. Today, anybody who has a college degree can be a teacher (yet, it is not a clear-cut requirement) and who shows the document confirming that this person has passed severaldozen-hour pedagogical course that authorises to perform this profession. No profession where the public trust is conferred upon has the process of professional formation as simplified as this one. Other professions require professional apprenticeship that provide grounds for evaluation of this process as well as optimal fitness in terms of responsibility for its performance.